Study of molecular vibration by coupled cluster method: bosonic approach - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Proceedings of the International Conference of Computational Methods in Sciences and Engineering 2010 (ICCMSE-2010), 2015)
The vibrational coupled cluster method in bosonic representation is formulated to describe the molecular anharmonic vibrational spectra. The vibrational coupled cluster formalism is based on Watson Hamiltonian in normal coordinates. The vibrational excited states are described using coupled cluster linear response theory (CCLRT). The quality of the coupled cluster wave function is analyzed. Specifically, the mean displacement values of the normal coordinates <qi> and expectation values of the square of the normal coordinates <q(i)(2)> of different vibrational states are calculated. A good agreement between the converged full CI results and coupled cluster results is found for the lower lying vibrational states.</q(i)(2)></qi>
Keywords: CCLRT; Expectation values; Watson Hamiltonian